The regulation of megabanks : legal frameworks of the USA and EU - Parchimowicz, Katarzyna M. (Routledge research in finance and banking law., 2022)
"Global systemically important banks are the largest, most complex and, in the event of their potential failure, most threatening banking institutions in the world. The global financial crisis was a turning point for global systemically important banks, many of which contributed to the outbreak and severity of this downturn. The unfolding of the global financial crisis also revealed flaws and omissions in the legal framework applying to financial entities. In the context of global systemically important banks it clearly demonstrated that the legal regimes, both in the USA and in the EU, grossly ignored the specific character of these institutions and their systemic importance, complexity and individualism. As a result of this omission, these megabanks were long treated like any other smaller banking institution. Since the financial crisis legal systems have changed a lot since then on both sides of the Atlantic, global and national lawmakers have adopted new rules applying specifically to global systemically important banks to reduce their threat to financial stability. This book explores whether the regulatory frameworks related to G-SIBs are adequately tailored to their individualism in order to prevent them from exploiting overly general rules, as they did during the global financial crisis. Analysing the specific character and individualism of G-SIBs, in relation to their history, normal function, as well as their operations during the GFC the book the transformation of banking systems and the challenges and opportunities G-SIBs face, such as Big Tech competitors, climate-related requirements and the COVID-19 pandemic Taking a multidisciplinary approach which combines financial aspects of operations of G- SIBs and legal analysis the book describes G-SIB-oriented legal frameworks of the EU and the USA and assesses whether G- SIB individualism is adequately reflected, assessing trends in supervisory action when it comes to discretion in the G-SIB context to contribute to the ongoing discussions about international banking law, its problems and potential remedies to such persistent flaws"--